LINQ for Visual C# 2005 - Ferracchiati, Fabio Claudio (Apress : Imprint: Apress, 2007)
C# programmers of every level need to learn about LINQ (Language-Integrated Query), Microsoft's breakthrough technology for simplifying and unifying data access from any data source. With LINQ, you can write more elegant and flexible code, not just to access databases and files, but also to manipulate data structures and XML. LINQ for Visual C# 2005 is a short, yet comprehensive guide to the major features of LINQ. It thoroughly covers LINQ to Objects, LINQ to SQL, LINQ to DataSet, and LINQ to XML. It also details significant enhancements to C#, .NET, and ADO.NET. The book also includes plenty of working examples to demonstrate LINQ in action. There is no better source than this book for getting a head start on the future of these technologies.